A study on catalytic dimethyl ether production from synthesis gas with CO2 - Altınsoy, Necdet Semih. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Increasing concerns on the emissions of hazardous species have boosted efforts towards development of cleaner alternatives of the conventional, crude-oils based fuels. In this respect, dimethyl ether (DME) is envisioned as a promising replacement of the present fuels due its numerous benefits such as non-toxicity, SO2 and soot free combustion and compatibility with the existing fuel distribution and processing infrastructures. DME synthesis involves conversion of synthesis gas (H2+CO+CO2) on methanol synthesis and dehydration catalysts. If catalysts are present in the same reactor, used method is called direct DME synthesis, otherwise is called indirect DME synthesis. The present study involves the direct route, i.e. the physical mixture of Cu-ZnO/-Al2O3 and -Al2O3, catalysts for methanol synthesis and dehydration, respectively. Synthesis gas (syngas) is formulated either as CO+H2 or CO2+H2, with the latter being much less studied and technically more dicult. Catalyst configuration, GHSV and pressure tests were conducted when the carbon source in syngas was CO. Replacement of CO with CO2 necessitated a more active dehydration catalyst, which was obtained by impregnating PTA on -Al2O3. Relative amounts of the catalysts and molar inlet H2/CO2 ratio were also studied as additional parameters. Moreover, sorption assisted CO2-to-DME conversion was also investigated. For the mixed configuration of catalysts and sorbent (Zeolite 3A), 30 wt.% PTA impregnation on -Al2O3 and 3 g sorbent addition were found as the optimum case at 225 0C, 30 bar, H2/CO2 = 3, dehydration to synthesis catalysts ratio = 2, GHSV = ⇠ 1750 h-1. Sorbent addition led to a notable increase in CO2 conversion and DME yield without sacrificing from the exit DME molar flow rate. Sorption capacity recovery of the sorbent upon regeneration was also investigated.
Keywords: Carbon dioxide.; Methyl ether.